Islamic Legal Evaluation of Non-Cash Capital in Livestock Partnerships: A Case Study on Mattungka Sapi in Sinjai District - Arsyad, Nurfadillah; Amelia, Raines Indah Mutiara; Qayum, Abdul Rahman (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
Profit sharing is a facility that is often used by the community, including the community in Lasiai Village, East Sinjai District, Sinjai Regency. The profit sharing carried out by the people in Lasiai Village is the profit sharing "Mattungka Sapi". This study discusses the practice of implementing profit sharing in the Mattungka Sapi collaboration agreement with the community in Lasiai Village, East Sinjai District, Sinjai Regency, as well as the Mattungka Sapi production sharing cooperation system according to the views of the schools of jurisprudence (Imam of the Syafiiyah School and Imam of the Hanafiyah School). In implementing the community in Lasiai Village, it consists of two forms of cooperation, namely the village government with the community and the community with the community which uses three patterns/systems for profit sharing from mattungka cows. If viewed from the implication that the profit sharing for the mattungka cow is in accordance with the pillars and requirements of Islamic law. However, on the pillars and conditions of mudharabah applied by the people of Lasiai Village in the profit sharing of Mattungka cows, the two Imams of the Shafi'i and Hanafi schools have different views on this matter. This research is a descriptive qualitative research in the form of field research with empirical and normative juridical approaches. Data processing techniques in this study were carried out in three stages, namely data reduction, data presentation and drawing conclusions. The key informants in this study were the village government and the community in Lasiai Village, East Sinjai District, Sinjai Regency who were involved in a cooperation agreement for the production of mattungka cows. In this study it was found that, First, the implementation of the cooperation agreement for the results of mattungka sapi in Lasiai Village must be carried out with a written agreement in order to avoid disputes or disputes in the future. Second, owners and keepers are highly expected before entering into a cooperation agreement for the production of mattungka sapi, they need an understanding regarding profit-sharing rules in Islam in order to achieve justice for both parties and avoid things that can save.